TRI HITA KARANA IN EDUCATION CONTEXT: A LITERATURE REVIEW - I Gde Putu Agus Pramerta (Jurnal Santiaji Pendidikan (JSP), 2023)
This article aims to describe the importance of Tri Hita Karana (henceforth, THK) in the education context based on previous studies. This issue is important to be researched since there is a trend of considering THK for the betterment of education. An online-based literature review was used to get the primary data. The data are taken from free downloadable articles in scientific journals that focus on THK and its values in the education context. Google Scholar and Connected Papers were used as the search engines. The articles were limited from 2018-2022 and searched with the keywords Tri Hita Karana, value, learning material, and education. In this study, the researcher defined the term THK, explained the values of THK in the education context, reviewed previous studies on the educational values of THK, and provided recommendations for the better multidisciplinary integration of THK in the education context, especially in English as a Foreign Language (EFL). The literature review indicated that, in the education context, THK is used as an indicator to be used for building character education and integrating it with classroom practice.